2007
DOI: 10.1128/jcm.00795-07
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of TwoKlebsiella pneumoniaeMastitis Outbreaks on a Dairy Farm in New York State

Abstract: Klebsiella spp. have become an important cause of clinical mastitis in dairy cows in New York State. We describe the occurrence of two Klebsiella mastitis outbreaks on a single dairy farm. Klebsiella isolates from milk, feces, and environmental sources were compared using random amplified polymorphic DNA (RAPD)-PCR typing. The first mastitis outbreak was caused by a single strain of Klebsiella pneumoniae, RAPD type A, which was detected in milk from eight cows. RAPD type A was also isolated from the rubber lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
113
1
10

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(133 citation statements)
references
References 32 publications
9
113
1
10
Order By: Relevance
“…rhinoscleromatis 4 (1.6%) ( Table 2). This seems to coincide with observation of Munoz et al (2007) who found that Klebsiella pneumoniae subsp. pneumoniae was predominant isolate (25% of cases) from 56 animal suffering from clinical mastitis.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…rhinoscleromatis 4 (1.6%) ( Table 2). This seems to coincide with observation of Munoz et al (2007) who found that Klebsiella pneumoniae subsp. pneumoniae was predominant isolate (25% of cases) from 56 animal suffering from clinical mastitis.…”
Section: Discussionmentioning
confidence: 63%
“…These results agreed to great extent with the finding of Hiroi et al (2012) who isolated Klebsiella pneumoniae from nasal swabs and bronchial mucous collected from calves suffering from bronchopneumonia. Moreover, Munoz et al (2007) reported that Klebsiella pneumoniae had been isolated from faecal samples of diarrhoeic calves.. As regard to sheep samples in this study Klebsiella pneumoniae was mainly predominant in faecal samples, nasopharyngeal swabs and milk samples 40.9, 17.4 and 14.3%, respectively. Shahrzad et al (2013) isolated Klebsiella pneumonia from lung of sheep suspected to be infected with pneumonia in an incidence of 15.09% and Gameel et al (1991) isolated Klebsiella pneumoniae subsp.…”
Section: Discussionmentioning
confidence: 77%
“…The diagnostic potential of RAPD technique has been successfully demonstrated for the description of genetic variation of microorganisms, higher plants, invertebrates, and vertebrates. [7][8][9][10] The most detailed RAPD analysis was performed for crops, livestock, and laboratory animals for the identification and differentiation of breeds and individual lines, chromosomal mapping, and identification of commercially valuable characters. [7][8][9][10] The studies of Dil-Afroze 11 and Ong 12 demonstrated the applicability of RAPD analysis for the detection of genetic instability in brain and lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…However, in vitro susceptibility tests have been shown to be poor predictors of treatment outcomes [1]. Such clinical outcomes are likely to be either a complication of cases of mastitis by different multidrug-resistant opportunistic pathogens previously invading the udders or the evolution of resistance mechanisms in the causative agent during therapy through mutations or lateral dissemination of antibiotic resistance determinants.Molecular epidemiological studies together with application of strict hygienic measures are only now being implemented in dairy farms all over the world as a result of mastitis outbreaks [12]. Given that the penetration of coliforms into the bovine teat duct during intermilking periods has been well documented [4,20], a better understanding of the antibiotic resistance mechanisms in the bacteria responsible for such asymptomatic cases is needed.…”
mentioning
confidence: 99%
“…Molecular epidemiological studies together with application of strict hygienic measures are only now being implemented in dairy farms all over the world as a result of mastitis outbreaks [12]. Given that the penetration of coliforms into the bovine teat duct during intermilking periods has been well documented [4,20], a better understanding of the antibiotic resistance mechanisms in the bacteria responsible for such asymptomatic cases is needed.…”
mentioning
confidence: 99%